When did the Pyrenean shortening end? Insight from U–Pb geochronology of syn‐faulting calcite (Corbières area, France). (28th July 2021) - Parizot, Oriane; Missenard, Yves; Haurine, Frederic; Blaise, Thomas; Barbarand, Jocelyn; Benedicto, Antonio; Sarda, Philippe
Abstract: Absolute dating helps to define the age and duration of orogen building. Here we present new U–Pb ages of syn‐faulting calcites collected in the northern foreland basin of the Pyrenees. The studied area underwent deformation during the Eocene growth of the belt. This orogenic growth is considered to have persisted until the Late Oligocene, after which post‐orogenic processes prevailed. Microstructural analysis coupled with U–Pb dating of syn‐faulting calcite confirms the well‐known NW‐SE to N–S main shortening stage of the Pyrenean orogen during the Eocene (from 48.7 ± 2.2 to 43.2 ± 5.3 Ma). But our data further reveal NE‐SW shortening during the Miocene, ca . 16 Ma ago, that has never been seen in the northern Pyrenean foreland. We propose that this tectonic phase, now identified on both sides of the Pyrenean Belt, is a consequence of a stronger coupling between Africa, Iberia and Europe at this time.